Saladin Al-Ayyubi 's religious treatment (565 - 589 AH/ 1169 - 1192 AD) - الله, م. م. نهاد جلال حبيب الله حبيب (Sulaimani Journal for Humanities, 2025)
The emergence of Saladin Al-Ayyubi coincided with the bad external and internal conditions of the Muslims. On the one hand, the Muslims were in a heated conflict with the Crusader forces. On the other hand, the Muslims were suffering from sectarian conflicts, and the intellectual and doctrinal differences between them had reached the stage of political division. Despite these obstacles and problems, The emergence of Saladin al-Ayyubi led to many fundamental changes, including the end of the Fatimid Caliphate and the liberation of Jerusalem. One of the most prominent doctrines spread among Muslims during the period of the rule of Salah al -Din al -Aubi is the Shiite doctrine, which was represented by the virtue of the Fatimid state and the subcontractor of the subconscious. The strength of Saladin was that he was able to eliminate the Shiite sect, and that he unified the Sunni sect and moved to fight the external enemy, which was represented by the Crusaders.
Keywords: Saladin; Shiite; Ismaili; Hanbali; Shafii; Ashari; Sufism